Inter-State Relations In Kautilyan Arthasastra: Exploring the Principles and Tactics of Inter-State Relations (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Kautilya'sArthashastra describes not only the internal Administration but the externalbehavior of the state also. All the basic principles of inter - state relationsare given in Arthashastra. He agrees with imperialism and describes the way towin a state. Kautilya deals with foreign policy, so he is popularly known asthe great theorist of interstate relations because of his unique andunprecedented contributation.1